Root proteases: reinforced links between nitrogen uptake and mobilization and drought tolerance - Kohli, Ajay; Narciso, Joan Onate; Miro, Berta; Raorane, Manish (Wiley, 2012)
Integral subcellular and cellular functions ranging from gene expression, protein targeting and nutrient supply to cell differentiation and cell death require proteases. Plants have unique organelles such as chloroplasts composed of unique proteins that carry out the unique process of photosynthesis. Hence, along with proteases common across kingdoms, plants contain unique proteases. Improved knowledge on proteases can lead to a better understanding of plant development, differentiation and death. Because of their importance in multiple processes, plant proteases are actively studied. However, root proteases specifically are not as well studied. The associated rhizosphere, organic matter and/or inorganic matter make roots a difficult system. Yet recent research conclusively demonstrated the occurrence of endocytosis of proteins, peptides and even microbes by root cells, which, hitherto known for specialized pathogenesis or symbiosis, was unsuspected for nutrient uptake. These results reinforced the importance of root proteases in endocytosis or root exudate‐mediated nutrient uptake. Rhizoplane, rhizosphere or in planta protease action on proteins, peptides and microbes generates sources of nitrogen, especially during abiotic stresses such as drought. This article highlights the recent research on root proteases for nitrogen uptake and the connection of the two to drought‐tolerance mechanisms. Drought‐induced proteases in rice roots, as known from rice expression databases, are discussed for future research on certain M50, Deg, FtsH, AMSH and deubiquitination proteases. The recent emphasis on linking drought and plant hydraulics to nutrient metabolism is illustrated and connected to the value of a systematic study of root proteases in crop improvement.